2021
DOI: 10.1186/s12920-021-01067-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CYP7B1 polymorphisms on the risk of coronary heart disease in Hainan Han population

Abstract: Background Coronary heart disease (CHD) is the leading cause of human death worldwide. Genetic factors play an important role in the occurrence of CHD. Our study is designed to investigate the influence of CYP7B1 polymorphisms on CHD risk. Methods In this case–control study, 508 CHD patients and 510 healthy individuals were recruited to determine the correlation between CYP7B1 polymorphisms (rs7836768, rs6472155, and rs2980003) and CHD risk. The as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…42 We found that rs1125970 and rs4897367 could be protective factors against CHD in people aged ≤60 years, but not in subjects aged >60 years. Similar results reported by Liang et al 43 have pointed out that CYP7B1 rs6472155 plays a risk-increasing role on CHD in individuals aged >60 years. Chen et al 44 have reported that NT5C2 rs2148198 can increase CHD risk in people aged ≤61 years.…”
Section: Discussionsupporting
confidence: 89%
“…42 We found that rs1125970 and rs4897367 could be protective factors against CHD in people aged ≤60 years, but not in subjects aged >60 years. Similar results reported by Liang et al 43 have pointed out that CYP7B1 rs6472155 plays a risk-increasing role on CHD in individuals aged >60 years. Chen et al 44 have reported that NT5C2 rs2148198 can increase CHD risk in people aged ≤61 years.…”
Section: Discussionsupporting
confidence: 89%
“…Signaling pathways include signaling by GPCR [56] and extracellular matrix organization [57] were responsible for advancement of HD. Research has shown that CBLN2 [58], MOG (myelin oligodendrocyte glycoprotein) [59], ROS1 [60], LGR6 [61], GJA5 [62], SUCNR1 [63], REN (renin) [64], VEGFC (vascular endothelial growth factor C) [65], TLR2 [66], FGF12 [67], WT1 [68], SLC22A3 [69], CSRP3 [70], PAPPA2 [71], ACAN (aggrecan) [72], SHH (sonic hedgehog signaling molecule) [73], PDC (phosducin) [74], AGTR1 [75], XDH (xanthine dehydrogenase) [76], P2RX7 [77], NTSR1 [78], SIRT2 [79], RBP4 [80], BMP2 [81], ERBB3 [82], HAS2 [83], CDH13 [84], CSMD1 [85], NR3C2 [86], EPAS1 [87], TRPC6 [88], MMP3 [89], ERAP2 [90], HLA-DRB1 [91], CD74 [92], VWF (von Willebrand factor) [93], MTTP (microsomal triglyceride transfer protein) [494], ANGPT2 [184], AKR1C3 [495], NEDD4L [496], CASP1 [497], LDB2 [498], CHRNA5 [499], CCND2 [500], BRCA2 [97], ZBTB20 [501], EFNB2 [502], CYP7B1 [503], DCLK1 [504], RBM20 [505], PLCE1 [197], protein) [94], NEDD4L [95], CASP1 [96], BRCA2 [97], EFNB2 [98], PLCE1 [99], EGFR (epidermal growth factor receptor) [100], ABCA1 [101], CRHR2 [102], RND3 [103], COMT (catechol-O-methyltransferase) [104] and SMAD9 [105] plays an important role in the pathogenesis of hypertension. Studies have revealed that NEUROD4 [106], SOX10 [107], MOG (myelin oligodendrocyte glycoprotein) [108], NR5A2 [109], GLRA3 [110], FA2H [111], SERPINA […”
Section: Discussionmentioning
confidence: 99%
“…FA2H [111], SERPINA1 [448], HOXB9 [113], TGM2 [449], LRRK2 [450], ROS1 [451], CFC1 [452], GDF3 [453], TF (transferrin) [121], RXFP1 [454], RELN (reelin) [455], HTR2C [456], MYL7 [457], DYSF (dysferlin) [458], GJA5 [459], IRX1 [460], TLL1 [461], SUCNR1 [462], KERA (keratocan) [463], TFAP2B [464], HOXA5 [465], ACSL6 [466], DSCAM (DS cell adhesion molecule) [467], MSR1 [468], REN (renin) [64], VEGFC (vascular endothelial growth factor C) [469], TLR2 [470], PCSK2 [471], FGF12 [472], SLC22A3 [142], HSPB7 [473], CSRP3 [474], KLRD1 [475], PTPRO (protein tyrosine phosphatase receptor type O) [476], IL7R [477], CUX2 [478], ACAN (aggrecan) [479], SHH (sonic hedgehog signaling molecule) [480], MEOX1 [481], AGTR1 [482], VTN (vitronectin) [483], SIRT2 [79], RBP4 [484], IL2RG [485], EPAS1 [486], CDH13 [487], TRPC6 [488], MMP3 [261], PCDHGA3 [489], FGF19 [490], TBX18 [491], HLA-DRB1 [492]. CD74 [493], VWF (von Willebrand factor) [267], MTTP (microsomal triglyceride transfer protein) [494], ANGPT2 [184], AKR1C3 [495], NEDD4L [496], CASP1 [497], LDB2 [498], CHRNA5 [499], CCND2 [500], BRCA2 [97], ZBTB20 [501], EFNB2 [502], CYP7B1 [503], DCLK1 [504], RBM20 [505], PLCE1 [197], EGFR (epidermal growth factor receptor) [276], ABCA1 [506], PDPN (podoplanin) [507], SCN4B [508], SLCO1B1 [509…”
Section: Discussionmentioning
confidence: 99%